ANALISIS NILAI-NILAI PENDIDIKAN KARAKTER DALAM BUKU TUNJUK AJAR MELAYU KARYA TENAS EFFENDY - Sayyidah Raihaninur; Otang Kurniaman; Eddy Noviana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract : This research is motivated by the increasing number of cases of social phenomena that we often see today, for example students who often skip classes during classes, students who often fight, promiscuity, drugs and other actions violate the norm. The need for character education needs that undermine the morals of the nation's children is embedded in everyday life. Character education encourages students to apply the values of goodness in real actions or daily behavior that relate to God Almighty, oneself, fellow human beings, the environment, and the nation and state. Quality characters need to be formed and nurtured from an early age. Early age, especially elementary age is a critical period for the formation of one's character. In this study, researchers examined the values of character education contained in the book